The ANALISIS KINERJA KEUANGAN PADA PEMERINTAH KOTA JAMBI PERIODE TAHUN 2020-2023 - Anggriani, Windi; Friyani, Rita; Safelia, Nela (Jurusan Akuntansi FEB Universitas Jambi, 2025)
This study analyzes the financial performance of the Jambi City Government for the period 2020–2023 using several key financial ratios: the Degree of Fiscal Decentralization, Regional Financial Independence, Financial Dependency, PAD Effectiveness, and Expenditure Efficiency. It also formulates strategies to improve regional financial performance through a SWOT analysis. The study employs a quantitative descriptive method based on APBD data, supported by qualitative analysis for strategy formulation. The findings show that the degree of decentralization and fiscal independence remain low, while financial dependency is consistently categorized as very high. PAD effectiveness is relatively good but fluctuates, and expenditure efficiency varies across the period. These results highlight the need to optimize PAD sources and strengthen expenditure management. The SWOT analysis produces strategies such as digitalizing PAD services, enhancing spending efficiency, strengthening collaboration with regional enterprises and the private sector, and improving fiscal accountability. Implementing these strategies is expected to enhance fiscal capacity and strengthen long-term financial independence for the Jambi City Government.